Children’s mental representations with respect to caregivers and post-traumatic symptomatology in Somatic Symptom Disorders and Disruptive Behavior Disorders - Bizzi, Fabiola; Cavanna, Donatella; Castellano, Rosetta; Pace, Cecilia S. (Frontiers in Psychology, 2015)
Introduction. In line with literature, the quality of adult-infant interactions and mental representations of the caregivers play an essential role in influencing the children’s well-being. Many studies focused the attention on the role of attachment for a better evaluation of child psychopathological outcomes. The flexibility of the child’s attachment model gives the opportunity to parents to be helped in modifying their own caregiving quality, encouraging the reflection on the children’s state of mind with respect to attachment. The aims of this study were to evaluate: 1) the attachment models in young patients diagnosed with Disruptive Behaviour Disorders (DBD) and Somatic Symptoms Disorders (SSD); 2) the levels of post-traumatic symptomatology; 3) the association between the attachment models and post-traumatic symptomatology. Methods. 40 Italian patients, aged from 8 to 15, recruited at Gaslini Paediatric Hospital of Genoa, previously diagnosed with SSD (N=20) and DBD (N=20) were assessed using the Child Attachment Interview (CAI), the Separation Anxiety Test (SAT), the Trauma Symptom Checklist for Children (TSCC-A). Socio-demographic data were collected. Results. In both the clinical samples, the findings on the distribution of attachment models showed a significant presence of insecure attachment with respect to both parents in more than a half of the patients and high levels of disorganized attachment. No significant differences between DBD and SSD samples were found on post-traumatic symptomatology (Post-Traumatic Stress and Dissociation). Significant differences were found on Depression, Anxiety and Fantasy subscales. Discussion. This study can provide a detection of dysfunctional aspects in clinical populations. The findings suggest that the quality of the attachment to parents may be a fundamental element to better assess SSD and DBD in children and adolescents. Clinical implications of this study aimed at improving parental caregiving are highlighted